A realist approach to the evaluation of complex mental health interventions. (20th July 2018) - Duncan, Craig; Weich, Scott; Fenton, Sarah-Jane; Twigg, Liz; Moon, Graham; Madan, Jason; Singh, Swaran P.; Crepaz-Keay, David; Parsons, Helen; Bhui, Kamaldeep
Summary: Conventional approaches to evidence that prioritise randomised controlled trials appear increasingly inadequate for the evaluation of complex mental health interventions. By focusing on causal mechanisms and understanding the complex interactions between interventions, patients and contexts, realist approaches offer a productive alternative. Although the approaches might be combined, substantial barriers remain. Declaration of interest: All authors had financial support from the National Institute for Health Research Health Services and Delivery Research Programme while completing this work. The views and opinions expressed therein are those of the authors and do not necessarily reflect those of the National Health Service, the National Institute for Health Research, the Medical Research Council, Central Commissioning Facility, National Institute for Health Research Evaluation, Trials and Studies Coordinating Centre, the Health Services and Delivery Research Programme or the Department of Health. S.P.S. is part funded by Collaboration for Leadership in Applied Health Research and Care West Midlands. K.B. is editor of the British Journal of Psychiatry.